Debates in Pancreatic Beta Cell Biology: Proliferation Versus Progenitor Differentiation and Transdifferentiation in Restoring β Cell Mass - Spears, Erick; Serafimidis, Ioannis; Powers, Alvin C.; Gavalas, Anthony (Frontiers in Endocrinology, 2021)
In all forms of diabetes, β cell mass or function is reduced and therefore the capacity of the pancreatic cells for regeneration or replenishment is a critical need. Diverse lines of research have shown the capacity of endocrine as well as acinar, ductal and centroacinar cells to generate new β cells. Several experimental approaches using injury models, pharmacological or genetic interventions, isolation and in vitro expansion of putative progenitors followed by transplantations or a combination thereof have suggested several pathways for β cell neogenesis or regeneration. The experimental results have also generated controversy related to the limitations and interpretation of the experimental approaches and ultimately their physiological relevance, particularly when considering differences between mouse, the primary animal model, and human. As a result, consensus is lacking regarding the relative importance of islet cell proliferation or progenitor differentiation and transdifferentiation of other pancreatic cell types in generating new β cells. In this review we summarize and evaluate recent experimental approaches and findings related to islet regeneration and address their relevance and potential clinical application in the fight against diabetes.